PHYSIOLOGICALLY-BASED PHARMACOKINETIC MODEL FOR PLANT-BASED ANTI-OXIDANT DRUGS - Viswanathan, Baskar; Tks, Shabeer; Chida, Afiya Razia; Stanly, Deepa Mary (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: A pharmacokinetic study is a cumbersome process in clinical research. It is very important in target validation and in shifting a lead compound into a drug. Our major objective was to reveal the most important physiochemical characters of the plant-based anti-oxidants in align with human physiology. The in silico studies can preferably be the best solution to identify the physiologically-based pharmacokinetic (PBPK) behavior of the anti-oxidants. Methods: Anti-oxidants are found in many foods including fruits and vegetables. Few of the important anti-oxidants, i.e. around 10 plant-based antioxidant compounds were taken for this research. These compounds were evaluated based on their pharmacokinetic parameters. The properties such as Lipinski’s rule of 5, absorption, distribution, metabolism, excretion, and toxicity (ADMET) of the compounds were screened thoroughly with the help of tools such as molinspiration and gastroplus. Results: The physiological studies of these compounds had shown different compartmental absorptions of the compound in the human gastrointestinal tract. Certain compounds were found to pass the physiological barriers and had the ability to become a drug. The compounds were filtered using the risk and toxicity factors. These risk factors caused the compounds to fail in the process of becoming a drug. Conclusion: The compounds which passed the PBPK studies were eligible to become a drug. Of the 10 compounds investigated, eugenol, gingerol, zingerone, and geraniol were found to have higher fraction of absorption to become a drug. Out of these compounds, the compounds gingerol and eugenol have shown the best factor of absorption, and hence, have a better probability of becoming a drug. Keywords: Anti-oxidants, Lipinski, Absorption, Distribution, Metabolism, Excretion and toxicity, Physiological properties, GastroPlus, In silico.